Physical activity level, dietary habits, and alcohol and tobacco use among young Guatemalan adults - Stein, Aryeh D.; Gregory, Cria O.; Hoddinott, John F.; Martorell, Reynaldo; Ramakrishnan, Usha; Ramirez-Zea, Manuel (SAGE Publications, 2005)
Physical activity, diet, and alcohol and tobacco use are all related to the development of obesity, diabetes, coronary heart disease, osteoporosis, and cancer. We examined the distribution of measures of these behaviors in a cohort of individuals born in four villages in Guatemala between 1962 and 1977 and who were 26–41 years old in 2003. Response rates to the instruments averaged 80% of cohort members known to be living in Guatemala. Physical activity levels were moderate, and were lowest among migrants to Guatemala City. Dietary habits reflect early phases of the nutrition transition, with high carbohydrate and moderate fat intakes. Migrants to Guatemala City reported higher intakes of meat and of dairy products, while those remaining in or near the original study villages reported higher consumption of tortillas and of vegetables and fruits. One-third of men reported consuming alcohol and 42% were current smokers. Very few women reported alcohol or tobacco use.